PEMANFAATAN BUAH MAHONI PADA MASYARAKAT DESA TEMBUNG, MEDAN ESTATE, LAUT DENDANG, KOLAM DAN PERCUT DI KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Syarifah Widya Ulfa; Alfina Sukma Hayati Damanik; Ayu Riski Aulia; Dini Indah Syahfitri; Putri Agustina Anggreni Arwira; Rifqi Khoir Afdan (STKIP Subang, 2023)
Mahogany plants are usually planted as shrubs or protective plants. Basically, this plant has many medicinal benefits, but there are still many people who don't know about the uses of this plant. The most widely used use is for the seeds, which are flat with a powdery coating and have a bitter taste. This aims to determine the medicinal properties contained in the mahogany plant. The type of research used by the author is a qualitative approach which is descriptive analysis. From the results of the research conducted, almost all residents interviewed knew about the benefits of mahogany fruit as a medicine for hypertension, where this tree has a high content of flavonoids, namely compounds that have antihypertensive effects. Flavonoids can help lower blood pressure by: Increasing the production of nitric oxide.